Fact Sheet “DOCA – Database of Variables for Content Analysis”. On the relevance, objective, content and participation possibilities of the database of variables for standardized content analysis - Franziska Oehmer-Pedrazzi; Sabrina H. Kessler; Edda Humprecht; Katharina Sommer; Laia Castro (Studies in Communication Sciences, 2023)
The Open Access Database of Variables for Content Analysis (DOCA) collects, systematizes, and evaluates operationalizations for standardized manual and automatic content analysis in the field of communication science. DOCA aims to facilitate researchers in finding suitable and established or tested operationalizations (as well as complete codebooks) for standardized content analysis. For communication science research, this is expected to result in increased comparability of content analytic studies and projects, as well as greater emphasis on the transparency of operationalizations and quality indicators. The present fact sheet is associated with two central objectives: firstly, to provide information about DOCA and its applications, thereby increasing awareness of this research infrastructure. Secondly, from the personal perspective of the editors, this article aims to outline the process and associated challenges involved in the conception, realization, and maintenance of a research database.